Prevention of Mother-to-child HIV Transmission in Nigeria: Six Years’ Experience from a Tertiary Institution - Jalo, Rabiu I.; Amole, Taiwo Gboluwaga; Dongarwar, Deepa; Abdullahi, Hadiza Musa; Tsiga-Ahmed, Fatimah Ismail; Gaya, Sule Abdullahi; Bello, Musa Mohammed; Bashir, Usman; Aminu, Aliyu; Kwaku, Aminatu Ayaba; Aliyu, Muktar Hassan; Salihu, Hamisu Mohammed; et al. (Current HIV Research, 2021)
Background: In line with global standards and progress made in Prevention of Motherto- Child Transmission (PMTCT), an assessment of the outcome of Early Infant Diagnosis in northern Nigeria is necessary to evaluate progress towards zero Human immunodeficiency Virus (HIV) infection among children. Objectives: This study assessed the infection rate and risk factors for mother-to-child HIV transmission among HIV-exposed children in Kano, northwest Nigeria. Methods: Using a retrospective cohort design, pregnant HIV-positive women and their exposed infants were recruited over a period of six years (2010 to 2016). Participants were enrolled during pregnancy or at delivery in the PMTCT clinic of a tertiary health facility in Kano, Nigeria. The main outcomes for the study were Early infant diagnosis positivity for HIV at 6 weeks and risk factors for positivity. Results: Of the 1,514 infants studied, early infant diagnosis was positive for HIV among 13 infants (0.86%). Infants whose mothers did not have antiretroviral therapy (adjusted Prevalence Ratio aPR = 2.58, 95%CI (1.85- 3.57)), who had mixed feeding (aPR = 12.06, 95%CI (9.86- 14.70)), and those not on antiretroviral prophylaxis (aPR = 20.39, 95%CI (16.04- 25.71)) were more likely to be infected with HIV. HIV-exposed infants on nevirapine and zidovudine prophylaxis were 95% and 74%, respectively, less likely to be infected with HIV. Conclusion: HIV infection rate remains high among HIV-exposed infants whose mothers did not receive PMTCT services. Scaling up proven interventions of early commencement of antiretroviral treatment for mothers, adherence to antiretroviral prophylaxis, and avoidance of mixed feeding among HIV-exposed infants would protect future generations from HIV infection.
Keywords: antiretroviral therapy